Estudio de mejora de los procesos del área logística de la empresa América Móvil Perú S.A.C. durante los años 2015 al 2019 enfocados a la reducción del gasto total de operación - Velarde Lopez, Luis Rodolfo (2020)
During the year 2015, the environment surrounding America Movil Peru S.A.C. was characterized by high competition which generated a price war that affected all telecommunications operators and reduced drastically their levels of profitability. Under these circumstances, the company had been losing EBITDA points dramatically. Not being able to find the remedy through the income recovery option, America Movil initiated a search of options and projects within each department, that would become the main focus of each team during the ongoing year and the years to come. In 2011 America Movil Peru (Claro) merged with Telmex Peru, company owned by the same enterprise group, telecommunications fixed services supplier. As a result of this merge, and later absorption, Claro inherits from Telmex a property of almost 35 000 sqmts located at Avenida El Sol in the district of Villa El Salvador, where Telmex warehouses were operating managed by a third-party vendor. For this reason, the logistics department, whose duties included warehouses administration and distribution, proposed to the general management a savings project consisting of removing all inventories in the Ransa facilities and relocating them in a new warehouse that Claro would build at the newly obtained property in Villa El Salvador. This proposal would bring annual savings of about 3 000 000 US dollars that was the cost that Ransa represented to Claro in Lima operation. Additionally, all warehousing and distribution processes would be reviewed finding in them improvement opportunities that were put into effect with the consequent savings they provided. The required investment for the construction and implementation of this warehouse was 3 000 000 US dollars. That means that OPEX was replaced by CAPEX in search of the objective. The total logistics expenses, that at the end of the year 2014 had reached 104 million soles, became a total of 53 million soles by the end of the year 2019, as a result of all the implemented improvements.